Impact of cognitive decline on the physical functioning of older adults in Southern Brazil: a cross-sectional study - Gonçalves, Andréa Kruger; Martins, Valéria Feijó; Kanitz, Ana Carolina; Martinez, Flávia Gomes; Peyré-Tartaruga, Leonardo Alexandre; Castilhos, Raphael Machado; Haas, Aline Nogueira (Frontiers in Aging Neuroscience, 2025)
IntroductionReduced physical function has been linked to cognitive decline, yet this relationship remains understudied in the older Brazilian population. This study evaluates the impact of cognitive decline on physical functioning in older adults in Southern Brazil.MethodsA cross-sectional analysis was conducted with community-dwelling older adults (n = 336), categorized as cognitively unimpaired (CU, n = 181), mild cognitive impairment range (MCI-range, n = 105), or dementia-range (n = 50) based on Montreal Cognitive Assessment cutoff points adapted for the Brazilian population. Physical function was assessed using tests for balance, strength, flexibility, and aerobic endurance. Statistical analyses included one-way ANOVA with post hoc Bonferroni tests.ResultsMost physical function variables worsened as cognitive impairment increased. The CU group performed significantly better than the MCI- and dementia-range groups in dynamic and static balance, upper-body strength (η2 = 0.09), upper- and lower-body flexibility (η2 = 0.07, η2 = 0.08), and aerobic endurance (η2 = 0.11) (p < 0.05).ConclusionCognitive status influences physical function in older adults. Identifying physical indicators linked to cognitive decline may improve screening efforts in clinical trials.